Uang Kuliah Tunggal Berbasis Asuransi Sebagai Kebijakan Hukum Mengenai Hak Atas Pendidikan - Adam Adi Prawira; Mochammad Ramadhan Saputra; Diky Riansyah (Universitas Islam Indonesia, 2021)
The community's economic difficulties during the COVID-19 pandemic have an impact on the education sector, especially the ability of students to pay the Single Tuition Fees (UKT). Seen from the perspective of human rights, the right to obtain education will hence be limited. The formulation of the problem in this research is first, how is the legal protection related to the payment of Single Tuition Fees (UKT) during the covid-19 pandemic as outlined in the form of regulation? Second, how is the responsive and fair concrete method related to the application of the Single Tuition Fee (UKT) in fulfilling the right to education during the handling of the COVID-19 pandemic in Indonesia? The research method used is juridical-normative analyzing through secondary legal materials and compiled in a descriptive-analytical manner. The results of this study are first, the legal protection contained in Permendikbud No. 25 of 2020, Decree of the Chancellor of UII No. 363/SK-REK/SP/VI/2020 in conjunction with the Regulation of the Chancellor of Universitas Islam Indonesia Number 10 of 2020, the Regulation of the Chancellor of the University of Brawijaya Number 40 of 2020, have not been responsive and equitable for the fulfillment of the right to education. Second, responsive and fair concrete methods in fulfilling the right to education during the COVID-19 pandemic by using the principle of indemnity, which is the principle that regulates the provision of insurance-based compensation.Keywords: Covid-19 pandemic; human rights; insurance; indemnity principle; single tuition feeAbstrakKesulitan ekonomi masyarakat selama masa pandemi covid-19 berdampak pada sektor pendidikan, khususnya kemampuan mahasiswa dalam membayar Uang Kuliah Tunggal (UKT). Apabila ditarik dari perspektif HAM, hak untuk memperoleh pendidikan yang dinikmati oleh mahasiswa akan merasa terbatasi. Rumusan masalah dalam penelitian ini adalah pertama, bagaimana perlindungan hukum terkait dengan pembayaran Uang Kuliah Tunggal (UKT) selama pandemi covid-19 yang dituangkan dalam bentuk regulasi? Kedua, bagaimana metode konkrit yang responsif dan berkeadilan terkait dengan pembebanan Uang Kuliah Tunggal (UKT) terapannya dalam pemenuhan hak atas pendidikan selama penanganan pandemi COVID-19 di Indonesia? Metode penelitian yang digunakan adalah yuridis-normatif dengan dianalisa melalui bahan hukum sekunder dan disusun secara deskriptif-analitis. Hasil dari penelitian ini menyimpulkan pertama, perlindungan hukum yang termuat dalam Permendikbud No. 25 Tahun 2020, SK Rektor UII No. 363/SK-REK/SP/VI/2020 juncto Peraturan Rektor Universitas Islam Indonesia Nomor 10 Tahun 2020, Peraturan Rektor Universitas Brawijaya Nomor 40 Tahun 2020 secara implementatif belum responsif dan berkeadilan bagi pemenuhan hak atas pendidikan. Kedua, metode konkrit yang responsif dan berkeadilan dalam pemenuhan hak atas pendidikan selama pandemi covid-19 menggunakan asas indemnitas, yaitu prinsip yang mengatur mengenai pemberian ganti kerugian berbasis asuransi.Kata Kunci: Hak asasi manusia; asuransi; uang kuliah tunggal; asas indemnitasl pandemi covid-19